Breast cancer sourcebook basic consumer health information about breast health and breast cancer ... - Bellenir, Karen; ebrary, Inc. (Detroit, MI : Omnigraphics, 2009)
"Provides basic consumer health information on risk factors, prevention, diagnosis, and treatment of breast cancer, along with facts about coping after treatment. Includes index, glossary of related terms and directory of resources"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Breast -- Cancer -- Popular works; Electronic books